Exploring the Relationship Between Burnout and Job Satisfaction Among Clinical Nurses - Lee, Yu-Hsia; Lin, Mei-Hsiang (European Scientific Journal, ESJ, 2019)
Aim. The purpose of this study was to explore the associations between burnout and job satisfaction among clinical nurses. Methods: A cross-sectional survey of 295 nurses were recruited from a medical center in Taiwan. Surveys were conducted using a demographic questionnaire, a Job Satisfaction Scale, and a Job Burnout Inventory. Results: The results were as follows: (1) both of the â€œpersonal burnoutâ€ and â€œexternal satisfactionâ€ had the highest mean subscale score; (2) there were significant differences in the â€œwork-related burnoutâ€ and the â€œoverall burnoutâ€ related to those having children among the participating nurses (t=2.13, 2.10 p < .05); (3) there was a statistically significant relationship between the burnout, and the job satisfaction; (4) â€œpersonal burnoutâ€, â€œwork-related burnoutâ€, and the â€œovercommitment to workâ€ were related to the â€œinner satisfactionâ€ and the â€œexternal satisfactionâ€ (p < .05). Conclusion: This studyâ€™s findings may well provide guidance for the decision-making, and evidence for the need to improve job satisfaction in order to reduce burnout that may encourage nursing staff to retain their present jobs and improve the quality of care provided.